An Eccentricity for Improvement in Rice Stem Borer Detection Using Sensed Drone Imaging - Indrabayu, -; Basri, -; Achmad, Andani (Society of Visual Informatics, 2025)
Rice stem borers are severe pests that cause significant crop losses. This research aimed to tackle this problem by using a drone equipped with a high-resolution camera to capture detailed images of paddy fields. These images were then processed to estimate the early potential attacks of stem borer pests through color segmentation computing. The detection process relied on analyzing color variations, particularly focusing on symptoms indicative of stem borer presence. The system utilized Hue, Saturation, Value (HSV) color segmentation and advanced image processing algorithms on numerous rice field videos collected from drone flights conducted at altitudes ranging from 5 to 40 meters above the ground. To improve detection accuracy, the study tested the system with and without the eccentricity parameter, which is crucial in eliminating false positives caused by the misidentification of field embankments as stem borers. This research's primary contribution is the implementation of eccentricity, which significantly reduces the false-positive rate. The results demonstrated that the accuracy of the system with the eccentricity parameter included was 75%, compared to a significantly lower accuracy rate of 17.19% when the eccentricity parameter was not used. Overall, this study highlights the effectiveness of using drones for remote sensing and the importance of incorporating eccentricity in image processing algorithms to enhance the precision of early stem borer detection in rice fields. This approach not only improves the reliability of pest detection but also offers a promising method for protecting rice crops from severe pest damage.